Learning How: Body techniques and the consumption of experience - Murphy, Stephen (My University, 2018)
Although the skilful body has been ever-present in research accounts of consumption experiences, no sustained attention has been given to the acquisition of skills necessary for successful engagement with those experiences. In the present study, we report an empirical investigation of the acquisition and diffusion of embodied competencies amongst high-speed motorcyclists. In doing so, we mobilise the concept of reflexive body techniques in order to unpack the social, physical and mindful aspects of skilled embodiment. We demonstrate that skill acquisition is a necessary precursor to successful immersion into certain kinds of consumption experiences offered by the marketplace. Further, we underline the role of skill acquisition in subject formation.
PUBLISHED
Keywords: Skill acquisition; Body techniques; Embodiment; Body; Habitus; Experience; Phenomenology; Perception; Motorcycling; Observant participation; Identities in Transformation; Consumer behaviour, society